1974
DOI: 10.1099/00221287-83-2-207
|View full text |Cite
|
Sign up to set email alerts
|

A Co-operative Numerical Analysis of Nonscoto- and Nonphotochromogenic Slowly Growing Mycobacteria

Abstract: A co-operative taxonomic study has been performed on slowly growing nonpigmented mycobacteria (Run yon's group 111). Phenetic data on 89 strains, studied in 18 laboratories, were collected and analysed by a numerical taxonomic method. A variety of immunological properties, lipid analyses and measures of pathogenicity were analysed independently to establish correlation with numerical classification. Mycobacterium gastri, M . nonchromogenicum, M . terrae, M . avium and M . xenopi were recognized by almost all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…Wayne (47) showed subsequently that M. avium and the Battey bacillus were not separable from each other. Meissner et al (18) made the same observation. Marks et al (16) showed the similarity of the lipid composition of M. avium, M. intracellulare, and M. scrofulaceum.…”
Section: Growth On Medium Containing 02\ P-emrnosalicylatesupporting
confidence: 69%
“…Wayne (47) showed subsequently that M. avium and the Battey bacillus were not separable from each other. Meissner et al (18) made the same observation. Marks et al (16) showed the similarity of the lipid composition of M. avium, M. intracellulare, and M. scrofulaceum.…”
Section: Growth On Medium Containing 02\ P-emrnosalicylatesupporting
confidence: 69%
“…nonchromogenicum and M . terrae were considered to be closely related but of two different species (18). The results of our study suggest that these are differentiable by their patterns, although the patterns are of considerable similarity.…”
Section: Discussionmentioning
confidence: 41%
“…nouum was considered to be a synonym of M . terrae in an IWGMT study (18), these two showed slightly different patterns (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In neither study did such tests meet our criteria for inclusion in the published reports. Nevertheless, tests for the ability of an organism to grow a t 25 and 45°C appear to provide useful information (4). As indicated in Results, the poor reproducibility observed in some laboratories appeared to reflect inadequate control of temperatures.…”
Section: Discussionmentioning
confidence: 91%